(untitled)
Usually, ortho lithiation of Kagan's template 1 and quenching with electrophiles leads highly diastereoselectively to planar-chiral 1,2-disubstituted ferrocenes. Surprisingly, lithiation of 1 with lithium diisopropylamide (LDA) followed by addition of paraformaldehyde afforded regioisomer (+)-[S(S)]-[4-(2-hydroxyethyl)phenyl]sulfinyl)ferrocene (2), which was converted to (+)-[S(S)]-4-2-[(methylsulfonyl)oxy]ethyl)phenyl)sulfinylferrocene (3) (Scheme 1). The desired diastereoisomer (l)-1-(hydroxymethyl)-2-(p-tolylsulfinyl)ferrocene (5) in turn could also be obtained by ortho lithiation of 1 with LDA but by quenching with DMF to yield aldehyde 4 first, which then was reduced with NaBH4 to 5. Finally, target compound (l)-1-[(dimethylamino)methyl]-2-(p-tolylsulfinyl)ferrocene (6) was obtained by substitution of the OH group of 5 under mild conditions or directly by ortho lithiation of I with lithio-2,4,6-triisopropylbenzene (= 2,4,6-triisopropylphenyl)lithium; LTP) followed by quenching with N, N-dimethylmethyleneiminium chloride. At low temperatures, reaction of 1 with LDA leads, via the preferred diastereoisomeric transition state 'exo'-7 and under extrusion of a (diisopropylamine)lithium complex of type 8, in a highly selective manner, to diastereoisomeric ortho-lithiated chelate (l)-9 (Scheme 2). The reaction of I to 2 is explained by a rearrangement of (l)-9 to [S(S)][4-(lithiomethyl)phenyl]sulfinylferrocene 10, which is acid-catalyzed by coordinated diisopropylamine in complexes of type 8. This rearrangement is not observed if LTP is used as base or, in case LDA is applied, if the electrophile is sufficiently reactive at low temperatures., author = Heinemann, Frank Wilhelm and et al., author_hint = Weber I, Heinemann FW, Zenneck U, faupublication = yes, journal = Helvetica Chimica Acta, month = Jan, pages = 820-833, peerreviewed = Yes, support_note = Author relations incomplete. You may find additional data in field 'author_hint', title = A synthesis detour to planar-diastereoisomeric ferrocene derivatives around an unexpected rearrangement of ortho-lithiated Kagan's template [S(S)]-(p-tolylsulfinyl)ferrocene, volume = 90, year = 2007